Requirements Specification of a Machine Learning-based Medical Software System - Breda, Bruno Garcia de Oliveira; Nakagawa, Elisa Yumi (Anais Estendidos do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS), 2026)
Medicine software systems have increasingly incorporated Machine Learning (ML) models, posing significant challenges for Software Engineering (SE), particularly in dealing with their requirements that could ensure qualities such as reliability and security. In this scenario, the main problem is the difficulty of specifying requirements that often change continuously, including in the context of an large research project in which ML-based medical systems have been developed and this work is part of. Additionally, there is no consensus on better techniques for this. Hence, the main objective of this work was to define techniques for requirements specification and apply them in a realworld ML-based medical system. To this end, we scrutinized the literature to select techniques for specifying requirements; following this, we applied them to a medical system for predicting patient’s respiratory health conditions in the context of the large project. As a result, the specified requirements were the key element to the successful development of the system. Hence, these techniques could be helpful for the development of other ML-based medical systems.